Review of Waste Management in Indonesian Small Islands in the Last Five Years (2018-2023) - Vitasari, Vitasari; Syakti, Agung Dhamar; Suryanti, Ani; Viruly, Lily; Jaaman, Saifullah Arifin; Lestari, Febrianti; Nevrita, Nevrita; Azizah, Diana (Jurnal Wilayah dan Lingkungan, 2024)
Indonesia is a maritime country composed of 16,771 islands consisting of large islands and small islands. One of the environmental problems that occur in small islands. Waste management is a shared focus because sources of water, soil and air pollution can come from waste. Waste management on small islands is very important because small islands have a much higher vulnerability than large islands.. This article aims to identify and analyze waste management in Indonesia's Small Islands and evaluate if its implementation has utilized the technology and concepts of the Industrial Revolution 4.0. Based on the findings of a review of 14 articles published from 2018-2023, with 15 islands as research objects, it was found that most of the small islands used as research objects had not managed their waste properly. The waste is eventually dumped into the sea. The unmanaged factor of this waste can be caused by the geographical conditions on the island which are bordered by the sea, the lack of waste management facilities, the limited land area on small islands and the low awareness and participation of the community in waste management. The rest, several islands have carried out the process of storage, processing, collection and destruction quite well. The waste is turned into handicrafts (bags and souvenirs), ecobricks, garden decorations and plant fertilizers for organic waste as well as the development of innovative waste into diesel fuel. Unfortunately, the intended application based on the Industrial Revolution 4.0 has not been reflected in waste management on these small islands. This is expected to be information and input for the government and managers as a model for other small islands in an effort to manage waste generation on the island's mainland and garbage contamination in the sea.